Hymenoptera diversity on porang (Amarphopallus muelleri) in Sukabumi. Issue 1 (January 2022) - Susilawati,; Puspitasari, M; Indriati, G; Pranowo, D
Abstract: Amorphophallus muelleri (porang) is a potential plant as a source of glucomannan. Glucomannan is beneficial as raw material in the sector of food, health, beauty, and industry manufacture so that it has a high economic value. The research objective was to study the diversity of Hymenopteran in the porang plantation. The study conducted at Pakuwon Experimental Garden and Indonesian Industrial and Beverage Crops Research Institute (IIBCRI) Integrated Laboratory from January to July 2020. The insect collection method was installed pitfall trap (PT) and yellow pan trap (YPT) on porang field. There were 12 pitfall traps, and Yellow Pan traps installed on porang plants and set for 24 hours while observed with intervals of 2 weeks. The collected insect was identified into morphospecies. The results showed that Hymenopteran on porang plants consisted of 100 morphospecies. The dominant morphospecies was Anoplolepis gracillepes . The diversity index (H`) of Hymenopteran insect was 2.28 and the evenness (E) was 0.50. Collected Hymenopteran identified as pollinators, predators, and parasitoids. The pollinators were Apidae and Halictidae, the predators were Formicidae and Sphecidae, while the parasitoid insects found were 13 families i.e Braconidae, Scelionidae, and Ceraphronidae, etc.